Web-Based Interactive Form One Science Tutorial (WIFOST): Using Animations to Facilitate the Process of Teaching Science - Syahrul Nizam, Junaini (Proceedings of the International Conference on Informatics 2004 (Informatics 2004), 2004)
Web-based environment is getting more popular as a mean of conveying information and knowledge in education. By incorporating multimedia element likes animation with web-based learning, the students is offered with precise vibrant environment that is either hidden or not available in mere static graphics. Web-based Interactive Form One Science Tutorial (WIFOST) is a web-based learning site aims to help students to understand important concepts of science through usage of animation. This paper presents the result of the WIFOST project and statistical data from the questionnaires. In the experiment, 20 students were asked to arrange the randomly shuffled sequence of animation images in the proper order. From the experiment, less than 30% of the students manage to arrange. This result shows static images alone cannot help student to understand the concepts of Science. In terms of animation effectiveness, the participants (n=40) are generally satisfied with more than 32 respondent (80%) gave excellent rating. In term of animation quality, 36 participants (90%) were satisfied. The findings indicate that carefully designed animation; by following good usability practice will be able to improve student’s ability to understand the complex science concept